COVID-19-Associated Maxillary Osteomyelitis: A Case Report - Atarbashi-Moghadam, Saede; Lotfi, Ali; Atarbashi-Moghadam, Fazele; Eftekhari-Moghadam, Parsa (Journal of Dental School, 2024)
Objectives Mucormycosis, a lethal opportunistic infection, is associated with high rates of morbidity and mortality. The pathogenesis of this disease appears to be multifactorial, with numerous factors contributing to its onset and progression, particularly in relation to COVID-19 infection. Case The presented case was a 41-year-old male who had a history of COVID-19 infection and had received high-dose corticosteroid therapy. He presented with a painless, extensive necrotic lesion on the right maxilla. Conclusion A biopsy confirmed the diagnosis of maxillary mucormycotic osteomyelitis associated with COVID-19. Overall, understanding this severe infection is crucial for accurate diagnosis and prompt treatment.